Contralateral necrotizing fascitis after left nephrectomy for emphysematous pyelonephritis - Alberto Fuentes; Pablo A Rojas; Felipe delValle; Carlidia Ortega; Juan Cristobal Bravo; Álvaro Kompatzki (IJU Case Reports, 2022)
Introduction Emphysematous pyelonephritis is an acute necrotizing infection of the renal parenchyma. The management is variable, extending to total nephrectomy in severe or refractory cases. Post‐nephrectomy complications are numerous and common, necrotizing fasciitis, and sepsis being among them. Case presentation We present a case of a 37‐year‐old woman with obesity and a previous left emphysematous pyelonephritis episode managed conservatively. The patient presented with a second left emphysematous pyelonephritis and underwent a left total nephrectomy. Two weeks later, the patient presented with a contralateral necrotizing fasciitis of the abdominal wall. Subsequently, the patient required several surgical debridement procedures and a vacuum‐assisted closure system treatment. Conclusion Emphysematous pyelonephritis is an aggressive infectious disease that requires high suspicion in patients at risk.